Thermoeconomic optimization of supercritical refrigeration system with the refrigerant R744 (CO2) - Kuznetsov, Mikhail; Kharlampidi, Dionis; Tarasova, Victoria; Voytenko, Evgeniy (Eastern-European Journal of Enterprise Technologies, 2016)
We developed a thermoeconomic model of refrigeration plant that works by the supercritical CO2 cycle as refrigerating medium. The model is built for the plant of the “air – air” type and makes it possible at the optimization of design and the selection of economical operating modes to simultaneously consider both thermodynamic and economic parameters. Resulting expenses for the creation and operation of the system over the projected life cycle were accepted as objective function for analysis of the model. The minimum of resulting expenses corresponds to the optimum system characteristics while maintaining amount and quality of produced cold. Development of the model allowed us to represent objective function in the form of expanded analytical expressions, which consider interrelation between all optimizing parameters of the system. One of the benefits of the method consists in the fact that the obtained unique analytical solution in the form of a system of equations of partial derivatives from objective function of the resulting expenses is applicable for the thermoeconomic optimization of regime parameters of operation of any refrigeration system that works according to the examined scheme and with a similar type of equipment. Numerical solution of the thermoeconomic optimization problem of refrigeration plant of the “air – air” type (conditioner), with CO2 as refrigerant, that works in the supercritical region made it possible to find optimum parameters of the system, which provide for the conditions of reaching minimum level of the resulting expenses at different values of tariffs for electric power. We examined effect of the value of tariff for electric power on the character of optimization of the system. An application of this technique in practice should contribute to the reduction in financial costs for the creation and operation of conditioners that work on CO2, to an increase in their competitivness compared with traditional freon systems and contribute to the creation of conditions for their large-scale implementation in Ukraine.